Simulating infrared spectro-photometric surveys with a Spritz. (17th December 2021) - Bisigello, L.; Gruppioni, C.; Calura, F.; Feltre, A.; Pozzi, F.; Vignali, C.; Barchiesi, L.; Rodighiero, G.; Negrello, M.; Carrera, F. J.; Dasyra, K. M.; Fernández-Ontiveros, J. A.; et al.
Abstract: Mid- and far-infrared (IR) photometric and spectroscopic observations are fundamental to a full understanding of the dust-obscured Universe and the evolution of both star formation and black hole accretion in galaxies. In this work, using the specifications of the SPace Infrared telescope for Cosmology and Astrophysics (SPICA) as a baseline, we investigate the capability to study the dust-obscured Universe of mid- and far-IR photometry at 34 and $70\, {\rm{μ }}m$ and low-resolution spectroscopy at $17{-}36\, {\rm{μ }}m$ using the state-of-the-art Spectro-Photometric Realisations of Infrared-selected Targets at all- z (Spritz ) simulation. This investigation is also compared to the expected performance of the Origins Space Telescope and the Galaxy Evolution Probe. The photometric view of the Universe of a SPICA-like mission could cover not only bright objects (e.g. $L_{IR}>10^{12}\, {\rm L}_{\odot}$ ) up to ${z}=10$, but also normal galaxies ( $L_{IR}<10^{11}\, {\rm L}_{\odot}$ ) up to $z\sim4$ . At the same time, the spectroscopic observations of such mission could also allow us to estimate the redshifts and study the physical properties for thousands of star-forming galaxies and active galactic nuclei by observing the polycyclic aromatic hydrocarbons and a large set of IR nebular emission lines. In this way, a cold, 2.5-m size space telescope with spectro-photometric capability analogous to SPICA, could provide us with a complete three-dimensional (i.e. images and integrated spectra) view of the dust-obscured Universe and the physics governing galaxy evolution up to $z\sim4$ .